Analisis Faktor-Faktor yang Mempengaruhi keputusan Pembelian Produk Makanan Berlabel Halal di Kalangan Masyarakat Kecamatan Syiah Kuala Banda Aceh - Ihsana, Kamalya; Hakim, Rahmad; Sulistyono, Setyo Wahyu (Journal of Islamic Economics Development and Innovation (JIEDI), 2021)
This study aims to determine the analysis of the factors that influence purchasing decisions for halal-labeled food products among the people of Syiah Kuala District. The formulation of the problem is; how is the analysis of the factors that influence the decision to purchase food products labeled halal among the Syiah Kuala District, Banda Aceh? The research is called qualitative research with a phenomenological approach. Data collection techniques are observation, interviews and documentation. The data analysis technique followed the Miles and Huberman interactive model. The results showed, there are 4 factors that can be analyzed in the decision to purchase food products labeled halal among the Syiah Kuala community, namely 1) religious factors, this factor is the most important factor, but besides being halal the food is also thayyib, not redundant, and brings benefit. 2) psychological factors, namely the Syiah Kuala community is worried about the non-halal of a product even though it has a halal logo printed, so they pay attention to the ingredients contained in the packaging. 3) social factors , this is driven by reference groups, families , and also the role of Ulama in the local area . 4) factors of culture , namely, because Islam is synonymous with local culture, people sometimes join in buying a product, without paying attention to the halal label.